2018
DOI: 10.1302/1863-2548.12.180081
|View full text |Cite
|
Sign up to set email alerts
|

Trends in slipped capital femoral epiphysis: Is the rate declining?

Abstract: Abstract:PurposeSlipped capital femoral epiphysis (SCFE) is an adolescent hip condition with a high risk of complication. The purpose of this study was to evaluate trends in treatment using a prospectively collected paediatric nationally representative database.MethodsA total of 9034 patients undergoing treatment for idiopathic SCFE were selected by querying the Healthcare Cost and Utilization Project’s Kids’ Inpatient Database for the years 1997, 2000, 2003, 2006, 2009 and 2012. The selected patients were sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…24 Recent studies have suggested a divergent relationship between SCFE incidence and increasing obesity rates. 25,26 Notably, a 27.5% decrease in SCFEs in the U.S. between 1997 and 2012 25 and a 34% decrease in SCFEs in Ontario, Canada, between 2002-2011. 26 The uncertainty around this relationship could be linked to the reliability of direct measurements and reporting of obesity by institutions.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recent studies have suggested a divergent relationship between SCFE incidence and increasing obesity rates. 25,26 Notably, a 27.5% decrease in SCFEs in the U.S. between 1997 and 2012 25 and a 34% decrease in SCFEs in Ontario, Canada, between 2002-2011. 26 The uncertainty around this relationship could be linked to the reliability of direct measurements and reporting of obesity by institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report a decline in the incidence of SCFE[ 10 - 12 ]. As obesity rates have been increasing, it is unusual for fewer children to suffer from SCFE.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have demonstrated a reduction in SUFE incidence in the United States and Canada. 41,42 Both studies concluded the reasons for this are unclear, and further epidemiological studies are required to determine if this is reflected in other geographical regions. Larger cohort studies are currently underway, specifically the United Kingdom-based British Orthopaedic Surgery Surveillance on SUFE, 43 and whilst the results of this study are yet to published, it will be interesting to see how our national data of Northern Ireland compares with a large prospective longitudinal cohort study.…”
Section: Discussionmentioning
confidence: 99%